Adrenalectomy improves MSG-induced obesity in rats by increasing UCP-1 levels in interscapular brown adipose tissue - Willian Nascimento de Souza Rodrigues; Ananda Malta; Naiara Cristina Lucredi; Patrícia Cristina Lisboa; Rosiane Aparecida Miranda; Rodrigo Vargas; Camila Benan Zara; Maria Natália Chimirri Peres; Nilton Rodrigues Teixeira Junior; Jurandir Fernando Comar; Paulo Cezar de Freitas Mathias; Rosana Torrezan (Acta Scientiarum: Biological Sciences)
The administration of monosodium glutamate (MSG) to neonates has been shown to result in hypothalamic damage and development of metabolic syndrome. The objective of this study was to investigate whether bilateral adrenalectomy (ADX) could alter sympathetic activity in adult MSG rats, with the potential to contribute to the improvement of metabolic syndrome by interfering with intermediary metabolism. Following a period of 99 days, the rats that received the control treatment and MSG were subjected to bilateral adrenalectomy (ADX). The following experimental groups were established, and designated as follows: CTL-SHAM, CTL-ADX, MSG-SHAM, and MSG-ADX. The subjects were 109 and 110 days-old at the time of the experiment. The assessment included murinometric and biochemical parameters, an intravenous glucose tolerance test (IVGTT), sympathetic nerve activity in interscapular brown adipose tissue (iBAT), and protein content of β3-adrenergic receptor (β3-ADR) and uncoupling protein 1 (UCP-1). The MSG rats presented metabolic syndrome, which was associated with lower sympathetic activity and a decreased content of the β3-adrenergic receptor when compared to the controls in iBAT. We can conclude that the lower β3-adrenergic receptor contributed to the maintenance of obesity in the MSG rats model. Although it has an adverse effect on the glucose tolerance of CTL-ADX animals, the typical features of metabolic syndrome in adult MSG rats were mitigated by ADX. These effects included an enhancement of UCP-1 in iBAT, a reduction in fat accumulation, and an improvement in glycemia, thereby contributing to an improvement in metabolic syndrome.